2014
DOI: 10.1002/edn.247
|View full text |Cite
|
Sign up to set email alerts
|

Perceived support from family and friends among adults with type 2 diabetes

Abstract: SummaryThe aim of this study was to describe how adults with type 2 diabetes perceive support provided by family and friends and how such support can influence their diabetes management. Diabetes management behaviours have been described as challenging, and many individuals with type 2 diabetes fail to attain optimal glycaemic control. It has therefore been suggested that support from family and friends is critical for effective diabetes management. However, there is little empirical evidence from a patient pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 27 publications
2
24
0
2
Order By: Relevance
“…). More than half the studies were conducted in high‐income countries ( n =25; Table ). Half of the studies ( n =22) focused on culturally and linguistically diverse or disadvantaged populations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…). More than half the studies were conducted in high‐income countries ( n =25; Table ). Half of the studies ( n =22) focused on culturally and linguistically diverse or disadvantaged populations.…”
Section: Resultsmentioning
confidence: 99%
“…Participants were mostly women (63.5%), and their mean age was 58.6 (± 5.8) years. Ten studies specifically investigated the experience of adults with Type 2 diabetes regarding the influence of family members on their diabetes management . Some studies that were not aimed at investigating family members also provided substantial contributions to the development of the themes .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, many qualitative and quantitative observational studies have reported that families can be influential on diabetes self-management (Weiler and Crist, 2009;Guell, 2011;hu et al, 2013;Samuel-Hodge et al, 2013;Oftedal, 2014;Choi et al, 2015;Mayberry, Harper and Osborn, 2016), and some have measured an association between family behaviours and diabetes self-management (Epple et al, 2003;Wen, Shepherd and Parchman, 2004;Schiøtz et al, 2011;Sankar et al, 2015;Soto et al, 2015). An examination of this evidence is required to provide greater insights to optimize families' involvement in diabetes self-management (Schafer, McCaul and Glasgow, 1986;Inzucchi et al, 2012;Torenholt, Schwennesen and Willaing, 2014;Baig et al, 2015).…”
Section: Introductionmentioning
confidence: 99%